Fractional orthotriple fuzzy rough Hamacher aggregation operators and-their application on service quality of wireless network selection - Muhammad Qiyas; Muhammad Naeem; Saleem Abdullah; Faisal Khan; Neelam Khan; Harish Garg (Alexandria Engineering Journal, 2022)
In order to ensure effective hand over management, network selection is very important. The process of selecting a network that offers a reliable and satisfactory service to the end user is known as network selection. Some existing approaches are utilized for network selection, however, they are reactive and can lead to erroneous conclusions due to inadequate information. These methods, however, have drawbacks due to their computational complexity and need for excessive and frequent hand over. Thus, we defined fractional orthotriple fuzzy Rough sets (FOFRSs), that can easily deal with ambiguity and insufficient information. The concepts of fractional orthotriple fuzzy rough Hamacher averaging and geometric operators are also introduced. The fundamental properties of the defined operators are discussed in detail. An algorithm to cope with uncertainty and ambiguity information for a multiple attribute group decision making (MAGDM) problem are proposed. Finally, a numerical example of the real-life is provided. The proposed method is compared to several existing methods, and the results show that the proposed method is more effective and helpful than the others.